Guide to a healthy home all you need to protect yourself and your family from hidden household dangers (Petaling Jaya Advantage Quest Publications, 2013)
"Identify and fix common safety issues; Uncover the hidden toxins in everyday items; Make your own healthy cleaning supplies; Protect your family beyond the home".
Originally published under the title, 'The Everything Guide to a Healthy Home'
Includes bibliographical references
Keywords: Home economics; Dwellings -- Environmental aspects; Housing and health